Fluid sources in basement-hosted unconformity–uranium ore systems: tourmaline chemistry and boron isotopes from the Patterson Lake corridor deposits, Canada. Issue 1 (2022) - Potter, Eric G.; Kelly, Colter J.; Davis, William J.; Chi, Guoxiang; Jiang, Shao-Yong; Rabiei, Morteza; McEwan, Brian J.
No abstract available